Mechanical and Fracture Property Estimation of a Structural Adhesive - J. E. C. Pinto; R. D. S. G. Campilho (Techniques and Innovation in Engineering Research Vol. 1, 2022)
It is not sufficient to understand the conventional mechanical properties, such as Young’s modulus (E), shear modulus (G), tensile strength (\(τ\)f) and shear strength (\(τ\)f) in order to predict crack propagation of an adhesive joint using advanced fracture mechanics-based techniques like cohesive zone models (CZM). Actually, estimating the tensile (GIC) and shear fracture energy (GIIC) is also necessary. The purpose of this work is to carry out the mechanical and fracture property characterization of a new structural two-component epoxy adhesive. With this purpose, four tests which were conducted: tensile testing to bulk specimens, shear testing with thick adherend shear tests (TAST), double-cantilever beam (DCB) and end-notched flexure (ENF). The test results were consistent with the manufacturer’s data, and they will make it possible to build bonded structures using this adhesive.